2014
DOI: 10.1016/j.peptides.2014.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Hemopressin, an inverse agonist of cannabinoid receptors, inhibits neuropathic pain in rats

Abstract: Direct-acting cannabinoid receptor ligands are well known to reduce hyperalgesic responses after nerve injury, although their psychoactive side effects have damped enthusiasm for their therapeutic development. Hemopressin (Hp) is a nonapeptide that selectively binds CB1 cannabinoid receptors (CB1 receptors) and exerts antinociceptive action in inflammatory pain models. We investigated the effect of Hp on neuropathic pain in rats subjected to chronic constriction injury (CCI) of the sciatic nerve, and explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…Although several papers now show pharmacological effects of hemopressin in mice, noteworthy without control over its bioavailability, (e.g. Toniolo et al, 2014;Dodd et al, 2013), it appears that hemopressin is not endogenously generated but its presence being the result of a hot extraction artefact derived from longer peptides (Gelman et al, 2010;Bauer et al, 2012). Furthermore, it seems that RVD-hemopressin (pepcan-12) is the major peptide endocannabinoid species found endogenously in the CNS and in the periphery (Bauer et al, 2012;Gelman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although several papers now show pharmacological effects of hemopressin in mice, noteworthy without control over its bioavailability, (e.g. Toniolo et al, 2014;Dodd et al, 2013), it appears that hemopressin is not endogenously generated but its presence being the result of a hot extraction artefact derived from longer peptides (Gelman et al, 2010;Bauer et al, 2012). Furthermore, it seems that RVD-hemopressin (pepcan-12) is the major peptide endocannabinoid species found endogenously in the CNS and in the periphery (Bauer et al, 2012;Gelman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, hemopressin has been shown to modulate nociceptive effects via complex mechanisms and to cause different pain modulations due to the differences of nociceptive assay models and injection sites [7,18]. Hemopressin has been shown to attenuate carrageenaninduced mechanical allodynia when administered by intrathecal, intraplantar and oral routes, and to inhibit neuropathic pain using chronic constriction injury model when administered by oral route [1,19]. Systemic injection of hemopressin also produced marked antinociceptive potency in the acetic acid-induced visceral nociception model [1].…”
Section: Discussionmentioning
confidence: 99%
“…is effective in mitigating mechanical allodynia in the CCI model (Lim, Sung, Ji, & Mao, 2003) while Costa et al (Barbara Costa et al, 2005) demonstrated that systemic administration of a CB1R antagonist significantly reduces mechanical and thermal hyperalgesia in CCI rats and in mice. Others (Toniolo et al, 2014) (Ueda et al, 2014) have also suggested that CB1R expression and activation can be maladaptive. Very recent research indicates that CB1R expression contributes to the development of persistent mechanical hypersensitivity, protects against the development of cold allodynia but is not involved in motor impairment following spared-nerve injury in mice (Sideris et al, 2016).…”
Section: Evidence From Neuropathic Pain Modelsmentioning
confidence: 99%